Coagulation assessment with thromboelastography during abdominal endovascular aneurysm repair in a patient with hemophilia A - Kazuki Sato; Nobuyuki Katori; Yoshifumi Suga; Shuya Kiyama; Shoichi Uezono (JA Clinical Reports, 2020)
Abstract Background As both APTT and APTT-based coagulation method cannot distinguish heparin effect from intrinsic coagulation factor deficiency, we implemented thromboelastography (TEG) for the coagulation assessment in a patient with hemophilia A undergoing an endovascular surgery with heparinization. Case presentation A 68-year-old male with hemophilia A underwent endovascular aortic repair for abdominal aortic aneurism. TEG results showed recovery of coagulation time (R) in both kaolin assay (CK) and kaolin-heparinase assay (CKH) after factor VIII replacement before heparinization. Against our expectations, R-CKH was slightly prolonged (9.0 min) during heparinization. After the administration of protamine sulfate, R in both assays showed similar values within the normal ranges. Conclusions The combination of CK and CKH assays could be useful to estimate factor VIII (FVIII) level when heparin concentration is low or without heparin; however, caution should be necessary for estimation of FVIII level by TEG under the effect of medium- or high-dose heparin.